Associations between the neighbourhood built environment and out of school physical activity and active travel: An examination from the Kids in the City study. (November 2015) - Oliver, Melody; Mavoa, Suzanne; Badland, Hannah; Parker, Karl; Donovan, Phil; Kearns, Robin A; Lin, En-Yi; Witten, Karen
Abstract: This study's aim was to examine selected objectively-measured and child specific built environment attributes in relation to proportion of out-of-school time spent in moderate-to-vigorous physical activity (%MVPA) and active travel in a group of ethnically and socio-economically diverse children ( n =236) living in Auckland, New Zealand. Street connectivity and distance to school were related to the proportion of trips made by active modes. Ratio of high speed to low speed roads and improved streetscape for active travel were related to %MVPA on weekdays only. Inconsistent results were found for destination accessibility. Local destinations (particularly schools) along a safe street network may be important for encouraging children's activity behaviours. Highlights: We examine associations between the built environment and children's %MVPA and travel. Participants were ethnically and socio-economically diverse living in Auckland, New Zealand. Street connectivity and distance to school were related to active travel on weekdays and weekend days. Ratio of high speed to low speed roads and improved streetscape were related to %MVPA on weekdays only. Local destinations along a safe street network may be important for encouraging children's activity.